The role of farmer's trust, risk and time preferences for contract choices: Experimental evidence from the Ghanaian pineapple sector - Sabine Fischer; Meike Wollni (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
In the last decades global food value chains have seen the need for increasing vertical coordination in order to secure quality standards. A prominent way to govern the relationships between farmers and agri-business firms are farming contracts. We study the role of trust, risk and time preferences for farmers' contract choices in a discrete choice experiment among Ghanaian pineapple farmers. We find that experimental measures of trust, risk and time preferences can predict preferences for contract attributes. Especially trust has economically important effects on the willingness to pay for transparent quality controls. Differences in preferences for timing of payment and timing of agreement making cannot be explained by trust levels but the time preferences. Risk-sharing in form of reduced quality requirements is less important for risk-seeking individuals compared to risk-neutral or risk-avers farmers. Including behavioral preferences can significantly improve the explanatory power of the models. Our results indicate that preferences affect farmers' participation constraints and argue that a diversification of contract offers might increase the willingness of farmers to participate in contract farming. This has implications for companies who aim at developing stable long-term relationships with farmers.
Keywords: O13; Q12; Q13; 330; lab in the field experiment; discrete choice experiment; contract choice; preferences; contract farming